Immunogenicity and potential protection of DNA vaccine of Leishmania martiniquensis against Leishmania infection in mice - Thuntawat Aunguldee; Orapin Gerdprasert; Piyatida Tangteerawatana; Amporn Jariyapongskul; Saovanee Leelayoova; Benjamas Thanomsub Wongsatayanon (Journal of Infection in Developing Countries)
Introduction: In Thailand, Leishmania martiniquensis is the predominant species causing cutaneous and visceral leishmaniasis. Its incidence has been increasing among immunocompetent and immunocompromised hosts. We developed a prototype DNA vaccine using a partial consensus sequence of the cysteine protease B (cpb) gene derived from L. martiniquensis from Thai patients.